2016
DOI: 10.1530/rep-15-0585
|View full text |Cite
|
Sign up to set email alerts
|

MFGE8 regulates TGF-β-induced epithelial mesenchymal transition in endometrial epithelial cells in vitro

Abstract: This study investigated the role of milk fat globule-epidermal growth factor-factor 8 (MFGE8) in TGF-β-induced epithelialmesenchymal transition (EMT) of endometrial epithelial cells. These were in vitro studies using human endometrial epithelial cells and mouse blastocysts. We investigated the ability of TGF-β to induce EMT in endometrial epithelial cells (HEC-1A) by assessment of cytological phenotype (by light and atomic force microscopy), changes in expression of the markers of cell adhesion/differentiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…TGF-β signaling has two major functions—the activation of SMAD signaling and non-SMAD pathways. Several non-SMAD signaling pathways have been implicated in the response to the full EMT process, including the PI3K/AKT, Ras/Raf/MEK/ERK, and Wnt/β-catenin signaling pathways (Figure 1) [116,117]. TGF-β interacts with the TGF-β receptor type I membrane receptor to phosphorylate the adaptor protein SRC homology 2 domain-containing-transforming A (SHCA).…”
Section: Epithelial-mesenchymal Transition (Emt) Signaling Pathwaymentioning
confidence: 99%
“…TGF-β signaling has two major functions—the activation of SMAD signaling and non-SMAD pathways. Several non-SMAD signaling pathways have been implicated in the response to the full EMT process, including the PI3K/AKT, Ras/Raf/MEK/ERK, and Wnt/β-catenin signaling pathways (Figure 1) [116,117]. TGF-β interacts with the TGF-β receptor type I membrane receptor to phosphorylate the adaptor protein SRC homology 2 domain-containing-transforming A (SHCA).…”
Section: Epithelial-mesenchymal Transition (Emt) Signaling Pathwaymentioning
confidence: 99%
“…In SMAD-mediated signaling, TGF-β directly binds to the membrane receptors, leading to the formation of the SMAD complex by activating SMAD2/3/4. In non-SMAD signaling pathways, TGF-β triggers the AKT/PI3K pathway, Ras/Raf/MEK/ERK signaling pathway, and Wnt/β-catenin signaling pathway in order to induce the expression of epithelial proteins [45,46]. Moreover, the TGF-β type I receptor interacts with the Src homology 2 domain-containing transforming protein 1 (SHC1) to activate the growth factor receptor-bound protein 2 (GRB2) and son of sevenless (SOS) in order to induce Ras/Raf/MEK/ERK signaling.…”
Section: The Role Of the Tgf-β Pathway In Breast Cancermentioning
confidence: 99%
“…A recently published study using an in-vitro model of attachment showed that treatment with ovarian steroid hormones resulted in changes of N-cadherin, E-cadherin and vimentin (mesenchymal cell markers) in Ishikawa cells, accelerated Ishikawa cell motility and increased JAR spheroid outgrowth. This strongly suggested activation of EMT ( Uchida et al , 2012 ; Yu et al , 2016 ). The conclusion of these authors collectively suggested that the ovarian steroid hormones and the implanting embryo (Jar spheroids mimicking trophoblast) induced EMT of EECs, which may play a key role in early human embryo implantation.…”
Section: Discussionmentioning
confidence: 89%